Effectiveness of Brief DBT-informed Group Therapy on Psychological Resilience: A Preliminary Naturalistic Study. Issue 1 (2nd January 2019) - Lee, Soonhee; Mason, Mark
ABSTRACT: This naturalistic study was designed to examine the effectiveness of a 4-week skill-based group therapy that focuses on building resilience. The group, informed by Dialectical Behavior Therapy (DBT; Linehan, 1993, 2015), targets general clients at college counseling centers and emphasizes mindfulness as a coping strategy to stress, cognitive rigidity, emotion dysregulation, and interpersonal difficulties. Results indicated that group members showed clinically significant improvement in psychological resilience and general mental health at the conclusion of group therapy. Implications are discussed.